Analysis of Color and Hardness of a Medical Silicone with Extrinsic Pigmentation after Accelerated Aging - dos Santos, Daniela Micheline; Borgui Paulini, Marcela; Silva Faria, Tamires Gabrielle; de Moraes Melo Neto, Clovis Lamartine; Freitas da Silva, Emily Vivianne; de Caxias, Fernanda Pereira; Bertoz, André Pinheiro de Magalhães; Coelho Goiato, Marcelo (European Journal of Dentistry, 2020)
Objective The aim of this study is to evaluate the color alteration and shore A hardness of a medical silicone with extrinsic pigmentation, before and after accelerated aging.Materials and Methods Twenty samples (Silastic Q7–4735) were made with an intrinsic pigmentation. This intrinsic pigmentation was composed of a pink pigment (H-109-P, Factor II) and an opacifier (ZnO). All samples had standardized dimensions (45-mm diameter and 2-mm thickness). Half of the 20 samples manufactured subsequently received an extrinsic pigment (Tan FE–215, Factor II). Therefore, two groups were created (n = 10): Group 1, group with intrinsic pigmentation and without extrinsic pigmentation (control) and Group 2, group with intrinsic and extrinsic pigmentation. Samples were submitted to color and Shore A hardness tests, before and after 1,008 hours of aging.Statistical Analysis Color alteration data were submitted to Student’s t-test (α = 0.05). Shore A hardness data were submitted to two-way analysis of variance and Tukey test (α = 0.05).Results The incorporation of the extrinsic pigment on the silicone did not affect its color (ΔE) when the two groups were compared (p = 0.232). Regarding the hardness test, the interaction between group and period did not interfere with the hardness results(p=0.599). However, the period factor showed that there was a reduction in the hardness of the silicone after aging (p < 0.05).Conclusion In this study, all the hardness and color results of the silicone used were clinically acceptable, regardless of the presence of extrinsic pigmentation.
Keywords: prosthesis; maxillofacial prosthesis; silicone elastomers